Fiscal stimulus and skill accumulation over the life cycle - Laure Simon (Bank of Canada, 2023)
Using micro data from the U.S. Consumer Expenditure Survey and Current Population Survey, I document that government spending shocks affect individuals differently over the life cycle. Young households increase their consumption after an expansionary shock while prime-age households reduce it, regardless of their level of income or debt. Productivity and wages increase significantly for young workers. To rationalize these findings, I develop a parsimonious New Keynesian life-cycle model where young agents accumulate skills on the job through a learning-by-doing process. An increase in government spending raises hours worked, which enhances skill accumulation, particularly among young workers who face a steep learning curve. The ensuing increase in the relative labor demand for young workers boosts their wages, thus stimulating their consumption.
Keywords: D12; D15; E21; E62; J11; J24; 330; Business fluctuations and cycles; Fiscal policy; Productivity